Proposal of Self Targeting Therapy of Mountain Ginseng Pharmacopuncture - Byung-Jun Cho; Ki-Rok, Kwon (Korean Pharmacopuncture Institute, 2011)
Objectives & Methods: This research may accounts for Self Targeting Therapy (STT) which is a peculiar operation of Mountain Ginseng Pharmacopuncture. The objectives include analysis of its mechanism and reporting of clinical cases. Results: 1. STT of Mountain Ginseng Pharmacopuncture refers to the function of curing and making a diagnosis of the disease by oneself. 2. The mechanism of STT is to pursue the latent illness and make the remedial action by oneself. In this process, the symptom of latent disease is outwardly expressed. 3. The most popular symptom expressed is manifestation of pecular sensation along the specific meridians. Then followed headache, dizziness, powerless and etc. Diverse symptoms can be expressed by a patient. 4. If the revealed symptoms are carefully observed, the cause of the disease or the patient state can be diagnosed easily. Conclusion: The mechanism of STT of Mountain Ginseng Pharmacopuncture can be a great asset in clinical trials. Other studies on STT of Mountain Ginseng Pharmacopuncture should be followed in the future.